2001
DOI: 10.3354/meps220047
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microbial communities in marine surface sediments by terminal-restriction fragment length polymorphism (T-RFLP) analysis and quinone profiling

Abstract: We characterized microbial communities from Japanese coastal sediments by using terminal-restriction fragment length polymorphism (T-RFLP) analysis and quinone profiling. Surface sediments (0 to 2 cm) were collected from 5 different locations, Tokyo Bay (S1: water depth 15 m), Sagami Bay (S2: 1520 m; S3: 1133 m), Suruga Bay (S4: 1290 m), and Nankai Trough (S5: 4023 m). The length of terminal-restriction fragments (T-RFs) was estimated by an automated DNA sequencer. The average fragment numbers (mean ± SD) esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
5
11
0
1
Order By: Relevance
“…(2001), which found from 27 to 73 TRFs. Both our study and the work by Urakawa et al . (2001) observed that the distribution of bacterial diversity was independent from water depth, thus suggesting that pressure does not represent a key driver controlling the overall ribotype abundance.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…(2001), which found from 27 to 73 TRFs. Both our study and the work by Urakawa et al . (2001) observed that the distribution of bacterial diversity was independent from water depth, thus suggesting that pressure does not represent a key driver controlling the overall ribotype abundance.…”
Section: Discussionsupporting
confidence: 94%
“…The top 1 cm of the sediment of all deep-sea stations revealed the dominance of the same ribotypes. This is consistent with results reported by Urakawa et al . (2001), who found few numerically important TRFs (such as 44, 60, 81 and 100 bp) to be present in all surface sediments investigated.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, the relative abundance of K 1 was greater than that of PQ‐9 in some marine sediment samples, while PQ‐9 constantly predominated in the lake sediment samples 11 . The photosynthetic quinones detected in the deep‐sea sediments were considered to be vertically transported in the water column 31,32 . Boetius et al 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Following digestion with restriction endonucleases, variably sized terminal fragments can be differentiated with high resolution (±1 base) through use of an automated DNA sequencer allowing researchers to generate 'fingerprints' of complex microbial communities (Liu et al 1997). This readily applied technique has been shown to be effective in the comparison of microbial assemblages in various marine and terrestrial environments (Urakawa et al 2001, Mummey & Stahl 2003, Gomez et al 2004). Both prokaryotic and eukaryotic diversity have been documented in specific oceanic regions, but not on global scales.…”
Section: Introductionmentioning
confidence: 99%